Outcomes of Bedside Nurse-Driven Interdisciplinary Antibiotic Stewardship and Infection Prevention Rounds. (4th October 2017) - Ha, David; Forte, Mary Bette; Nguyen, Kim; Ancheta, Vickie; Catipon, Nora; Chan, Sarah; Lira, Donna; Legge, Jessica; Olans, Rita; Gluckstein, Daniel; Desai, Mamta; Mourani, John; et al.
Abstract: Background: The bedside nurse is a frequently underutilized but potentially valuable contributor to antimicrobial stewardship. Minimal literature exists to demonstrate the impact of active intervention by bedside nurses in antimicrobial stewardship. We initiated bedside nurse-driven interdisciplinary rounds in a 31-bed inpatient telemetry unit of a community teaching hospital involving a pharmacist, infection preventionist and nurse practitioner. Rounds were focused on use of antibiotics, acid suppressants, urinary catheters and central venous catheters. Recommendations from rounds were communicated by the bedside nurse to the appropriate provider. Methods: This was a prospective, observational pre- and post-intervention study (6 months in each cohort) to characterize the impact of bedside nurse-driven interdisciplinary rounds on use of antibiotics, acid suppressants, urinary catheters and central venous catheters in a telemetry unit. Results: A total of 515 patient encounters occurred during rounds with 663 total therapies reviewed. Of these therapies 245 (37%) were antibiotics, 220 (33%) were acid suppressants, 159 (24%) were urinary catheters and 39 (6%) were central venous catheters. Mean monthly acid suppressant days of therapy per 1000 patient-days (DOT/1000PD) was significantly reduced in the pre- vs. post-intervention cohorts (592 vs. 375, P = 0.001). Reductions in mean monthly antibiotic DOT/1000PD (2858 vs. 2668, P = 0.134) and urinary catheter days (176 vs. 135, P = 0.087) were observed but were not statistically significant. Central venous catheter days were similar in the pre- vs post-intervention cohorts (100 vs. 96, P = 0.657). Conclusion: Our data demonstrate that bedside nurses can contribute to antimicrobial stewardship and infection prevention outcomes when actively supported by a trained interdisciplinary team. Further study of strategies to engage bedside nurses in such activities is warranted. Disclosures: All authors: No reported disclosures.